Six-phase Voltage Forming Method using the Largest Magnitude Space Vectors - Lipinskis, T.; Baskys, A.; Rutkauskas, A. (Elektronika ir Elektrotechnika, 2013)
In this paper, a six-phase voltage source inverter with a single-neutral star connected load is investigated. A space vector PWM (SVPWM), which uses largest magnitude vectors is proposed and implemented. Simulation results of the six-phase voltage source inverter (VSI), which uses the proposed SVPWM method, are compared to the results when a standard sinusoidal PWM scheme is used. Analysis of the results shows that proposed SVPWM scheme is suitable to form a six-phase sinusoidal output voltage. The main advantage of proposed SVPWM scheme is that it requires the same computational resources as the three-phase SVPWM. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5904